The Impact of a Semester-Long, Cell Culture and Fluorescence Microscopy CURE on Learning and Attitudes in an Underrepresented STEM Student Population - Jennifer Hurst-Kennedy; Michael Saum; Cindy Achat-Mendes; Allison D’Costa; Elisabeth Javazon; Shoshana Katzman; Ernest Ricks; Alessandra Barrera (Journal of Microbiology & Biology Education, 2020)
Georgia Gwinnett College (GGC) is an access institution with a diverse student body, located in metro Atlanta. To strengthen research skills, teach employer-valued cell biology laboratory techniques, and increase student engagement, a semester-long, inquiry-based CURE was developed and implemented in Cell Biology with Laboratory (BIOL3400K), a sophomore-level course, which serves as a “gateway” to all upper-level biology courses. This CURE centers on the investigation of a student-chosen experimental factor on the viability of cultured, mammalian cells. Through participation in this CURE, students gain experience in cell culture, fluorescence microscopy, and viability assays, and strengthen important research skills, such as literature searches, graphing, and data analyses. The impact of this CURE on student learning gains and attitudes was assessed using pre-/post-content exams and the Colorado Learning Attitudes about Science Survey (CLASS). Our data show that all students made significant content gains. Female students made larger learning gains than male students. Additionally, minority students performed better than majority students in some content areas. Student attitudes did not change, or in some cases were slightly more negative after the CURE. Overall, this CURE had a positive impact on students by engaging them in an inquiry-based laboratory experience.